Normobaric Hypoxia Exposure During Treadmill Aerobic Exercise After Stroke: A Safety and Feasibility Study - Kelly, Liam P.; Basset, Fabien Andre; McCarthy, Jason; Ploughman, Michelle (Frontiers in Physiology, 2021)
Objective: To evaluate the safety and feasibility of performing treadmill aerobic exercise in moderate normobaric hypoxia among chronic hemiparetic stroke survivors. Design: Observational study using convenience sampling. Setting: Research laboratory in a tertiary rehabilitation hospital. Participants: Chronic hemiparetic stroke survivors who could walk at least 10-meters with or without assistance and had no absolute contraindications to exercise testing. Intervention: Participants (3 male and 4 female) were asked to complete three normobaric hypoxia exposure protocols within a single session. First, they were passively exposed to normobaric hypoxia through gradual reductions in the fraction of inspired oxygen (FIO2 = 20.9%, 17.0%, and 15.0%) while seated (5-min at each level of FIO2). Participants were then exposed to the same reductions in FIO2 during constant-load exercise performed on a treadmill at 40% of heart rate reserve. Finally, participants completed 20-min of exercise while intermittently exposed to moderate normobaric hypoxia (5 x 2-min at FIO2= 15.0%) interspaced with 2-min normoxia intervals (FIO2= 20.9%). Outcome measures: The primary outcome was occurrence of adverse events, which included standardized criteria for terminating exercise testing, blood oxygen saturation (SpO2) <80%, or acute mountain sickness score >2. The increased cardiovascular strain imposed by normobaric hypoxia exposure at rest and during exercise was evaluated by changes in SpO2, heart rate (HR), blood pressure, and rating of perceived exertion (RPE). Results: One participant reported mild symptoms of nausea during exercise in normobaric hypoxia and discontinued participation. No other adverse events were recorded. Intermittent normobaric hypoxia exposure was associated with reduced SpO2 (MD= -7.4%, CI: -9.8 to -5.0) and increased HR (MD= 8.2, CI: 4.6 to 11.7) compared to intervals while breathing typical room air throughout the 20-min constant-load exercise period. The increase in HR was associated with a 10% increase in relative effort. However, reducing FIO2 had little effect on blood pressure and RPE measurements. Conclusion: Moderate normobaric hypoxia appeared to be a safe and feasible method to increase the cardiovascular strain of submaximal exercise in chronic hemiparetic stroke survivors. Future studies evaluating the effects of pairing normobaric hypoxia exposure with existing therapies on secondary prevention and functional recovery are warranted.